KEBIJAKAN PIDANA DALAM PERLINDUNGAN KORBAN TINDAK PIDANA KEKERASAN BERBASIS GENDER ONLINE - Ayu Ardhia Pramesti, Ratih; Maroni, Maroni; Raisa Monica, Dona (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
This study aims to analyze the main inhibiting factors in identifying and finding perpetrators of Online Gender-Based Violence (OGBV) crimes in Indonesia, as well as evaluating the effectiveness of existing criminal policies in providing protection to victims. The research method used is normative law by analyzing related laws and regulations, legal literature, and relevant publications. The results of the study identified several significant obstacles in handling OGBV, including limited capacity and investigative facilities for law enforcement officers, difficulties in collecting and authenticating digital evidence, anonymity of perpetrators in cyberspace, low reporting rates by victims due to fear and shame, and limited specific regulations and suboptimal law enforcement. Furthermore, this study examines the criminal policy in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence which specifically regulates OGBV, including definitions, sanctions, and victim protection mechanisms. Although this law is a step forward, this study highlights the need to strengthen implementation, increase the capacity of law enforcement officers, and provide more comprehensive support for victims to overcome challenges in handling OGBV in Indonesia.